Long Non-Coding, Micro, and Circular RNAs in Ovarian Cancer Metastasis: Pathways and Treatment Approaches - Gosia, Meeral; Doshi, Gaurav; Parab, Siddhi; Godad, Angel (Reproductive sciences (Thousand Oaks, Calif.), 2025)
Gynaecologic cancer is a major cause of death for women and the most well-known ovarian cancer (OC) has a high mortality rate. Given that the majority of ovarian cancer deaths are caused by metastatic tumors that have spread to nearby tissues, several biological processes, including angiogenesis and metastasis, have a role in the onset and course of these diseases. Numerous non-coding RNAs (ncRNAs) have been shown in recent studies to contribute to the invasion and metastasis of ovarian cancer by altering particular cellular pathways. Three forms of ncRNAs which are long non-coding RNAs, micro RNAs, and circular RNAs are the subjects of this review. miRNA is used as a potential biomarker such as miR-375 which is a serum exosome and also in therapeutics. lncRNA sponges with miRNA which sequesters and regulates tumor progression such as XIST miR-149-3p. circRNA targets proteins and regulates gene expression. This review provides an overview of the precise function of non-coding RNAs in the many pathways and molecular exchanges that contribute to the invasion and metastasis of malignancies. To increase the survival rate of OC patients, new approaches to ncRNA-targeted therapy are being utilised, including targeting lncRNAs and circRNAs and modulating the tumor microenvironment using exosomes.